Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This is a problem from "A Course of Pure Mathematics" by G H Hardy. Find the limit $$\lim_{x \to 0}\frac{x\sin(\sin x) - \sin^{2}x}{x^{6}}$$ I had solved it long back (solution presented in my blog here) but I had to use the L'Hospital's Rule (another alternative is Taylor's series). This problem is given in an introductory chapter on limits and the concept of Taylor series or L'Hospital's rule is provided in a later chapter in the same book. So I am damn sure that there is a mechanism to evaluate this limit by simpler methods involving basic algebraic and trigonometric manipulations and use of limit $$\lim_{x \to 0}\frac{\sin x}{x} = 1$$ but I have not been able to find such a solution till now. If someone has any ideas in this direction please help me out.

PS: The answer is $1/18$ and can be easily verified by a calculator by putting $x = 0.01$

share|improve this question
@ParamanandSingh: Did they do series expansions early on? $f(x) = 1/18-x^2/45+(569 x^4)/113400+O(x^6)$ –  Amzoti Jul 7 '13 at 5:45
No. It's easy if we could use both $\sin(s) = s - \dfrac{s^3}6 + \dfrac{s^5}{120} + o(s^6)$ and $x = \arcsin(s) = s + \dfrac{s^3}6 + \dfrac{3s^5}{40} + o(s^6)$. Let $s=\sin(x)$. Then \begin{align*} \lim_{x\to 0}\frac{x\sin(s)-s^2}{x^6} &=\lim_{x\to 0}\frac{(x-s)(\sin(s)-s)+s\left(\sin(s)-s\right)+s(x-s)}{x^6}\\ &=\lim_{x\to 0}\frac{ \left(\dfrac{s^3}6\right)\left(-\dfrac{s^3}6\right) + s\left(-\dfrac{s^3}6+\dfrac{s^5}{120}\right) + s\left(\dfrac{s^3}6+\dfrac{3s^5}{40}\right)}{x^6}\\ &=\lim_{x\to 0}\frac{\dfrac{-s^6}{36}+\dfrac{s^6}{120}+\dfrac{3s^6}{40}}{x^6} =\frac1{18}. \end{align*} –  user1551 Jul 7 '13 at 13:13
Out of curosity, where exactly is this problem found in the book? I've been trying to find it in my copy, but to no avail. –  Andrew D Jul 7 '13 at 19:30
Thanks to all the people who put in effort for solving the problem. I particularly like the detailed solution by robjohn which establishes the fundamental limit of $(x - \sin x)/x^{3}$ without going through L'Hospital. Although it is bit detailed, it seems to be the best. As to the comment from Andrew D, this is from 10th edition of the book and it asks "Prove that $\phi(x) = x\sin(\sin x) - \sin^{2}x$ is of the sixth order of smallness when $x$ is small; and find the limit of $\phi(x)/x^{6}$ as $x \to 0$" (check page no 207) –  Paramanand Singh Jul 8 '13 at 3:54

5 Answers 5

up vote 21 down vote accepted

Preliminary Results:

We will use $$ \begin{align} \frac{\color{#C00000}{\sin(2x)-2\sin(x)}}{\color{#00A000}{\tan(2x)-2\tan(x)}} &=\underbrace{\color{#C00000}{2\sin(x)(\cos(x)-1)}\vphantom{\frac{\tan^2(x)}{\tan^2(x)}}}\underbrace{\frac{\color{#00A000}{1-\tan^2(x)}}{\color{#00A000}{2\tan^3(x)}}}\\ &=\hphantom{\sin}\frac{-2\sin^3(x)}{\cos(x)+1}\hphantom{\sin}\frac{\cos(x)\cos(2x)}{2\sin^3(x)}\\ &=-\frac{\cos(x)\cos(2x)}{\cos(x)+1}\tag{1} \end{align} $$ Therefore, $$ \lim_{x\to0}\frac{\sin(x)-2\sin(x/2)}{\tan(x)-2\tan(x/2)}=-\frac12\tag{2} $$ Thus, given an $\epsilon\gt0$, we can find a $\delta\gt0$ so that if $|x|\le\delta$ $$ \left|\,\frac{\sin(x)-2\sin(x/2)}{\tan(x)-2\tan(x/2)}+\frac12\,\right|\le\epsilon\tag{3} $$ Because $\,\displaystyle\lim_{x\to0}\frac{\sin(x)}{x}=\lim_{x\to0}\frac{\tan(x)}{x}=1$, we have $$ \sin(x)-x=\sum_{k=0}^\infty2^k\sin(x/2^k)-2^{k+1}\sin(x/2^{k+1})\tag{4} $$ and $$ \tan(x)-x=\sum_{k=0}^\infty2^k\tan(x/2^k)-2^{k+1}\tan(x/2^{k+1})\tag{5} $$ By $(3)$ each term of $(4)$ is between $-\frac12-\epsilon$ and $-\frac12+\epsilon$ of the corresponding term of $(5)$. Therefore, $$ \left|\,\frac{\sin(x)-x}{\tan(x)-x}+\frac12\,\right|\le\epsilon\tag{6} $$ Thus, $$ \lim_{x\to0}\,\frac{\sin(x)-x}{\tan(x)-x}=-\frac12\tag{7} $$ Furthermore, $$ \begin{align} \frac{\tan(x)-\sin(x)}{x^3} &=\tan(x)(1-\cos(x))\frac1{x^3}\\ &=\frac{\sin(x)}{\cos(x)}\frac{\sin^2(x)}{1+\cos(x)}\frac1{x^3}\\ &=\frac1{\cos(x)(1+\cos(x))}\left(\frac{\sin(x)}{x}\right)^3\tag{8} \end{align} $$ Therefore, $$ \lim_{x\to0}\frac{\tan(x)-\sin(x)}{x^3}=\frac12\tag{9} $$ Combining $(7)$ and $(9)$ yield $$ \lim_{x\to0}\frac{x-\sin(x)}{x^3}=\frac16\tag{10} $$ Additionally, $$ \frac{\sin(A)-\sin(B)}{\sin(A-B)} =\frac{\cos\left(\frac{A+B}{2}\right)}{\cos\left(\frac{A-B}{2}\right)} =1-\frac{2\sin\left(\frac{A}{2}\right)\sin\left(\frac{B}{2}\right)}{\cos\left(\frac{A-B}{2}\right)}\tag{11} $$

Finishing Up: $$ \begin{align} &x\sin(\sin(x))-\sin^2(x)\\ &=[\color{#C00000}{(x-\sin(x))+\sin(x)}][\color{#00A000}{(\sin(\sin(x))-\sin(x))+\sin(x)}]-\sin^2(x)\\ &=\color{#C00000}{(x-\sin(x))}\color{#00A000}{(\sin(\sin(x))-\sin(x))}\\ &+\color{#C00000}{(x-\sin(x))}\color{#00A000}{\sin(x)}\\ &+\color{#C00000}{\sin(x)}\color{#00A000}{(\sin(\sin(x))-\sin(x))}\\ &=(x-\sin(x))(\sin(\sin(x))-\sin(x))+\sin(x)(x-2\sin(x)+\sin(\sin(x)))\tag{12} \end{align} $$ Using $(10)$, we get that $$ \begin{align} &\lim_{x\to0}\frac{(x-\sin(x))(\sin(\sin(x))-\sin(x))}{x^6}\\ &=\lim_{x\to0}\frac{x-\sin(x)}{x^3}\lim_{x\to0}\frac{\sin(\sin(x))-\sin(x)}{\sin^3(x)}\lim_{x\to0}\left(\frac{\sin(x)}{x}\right)^3\\ &=\frac16\cdot\frac{-1}6\cdot1\\ &=-\frac1{36}\tag{13} \end{align} $$ and with $(10)$ and $(11)$, we have $$ \begin{align} &\lim_{x\to0}\frac{\sin(x)(x-2\sin(x)+\sin(\sin(x)))}{x^6}\\ &=\lim_{x\to0}\frac{\sin(x)}{x}\lim_{x\to0}\frac{x-2\sin(x)+\sin(\sin(x))}{x^5}\\ &=\lim_{x\to0}\frac{(x-\sin(x))-(\sin(x)-\sin(\sin(x))}{x^5}\\ &=\lim_{x\to0}\frac{(x-\sin(x))-\sin(x-\sin(x))\left(1-\frac{2\sin\left(\frac{x}{2}\right)\sin\left(\frac{\sin(x)}{2}\right)}{\cos\left(\frac{x-\sin(x)}{2}\right)}\right)}{x^5}\\ &=\lim_{x\to0}\frac{(x-\sin(x))-\sin(x-\sin(x))+\sin(x-\sin(x))\frac{2\sin\left(\frac{x}{2}\right)\sin\left(\frac{\sin(x)}{2}\right)}{\cos\left(\frac{x-\sin(x)}{2}\right)}}{x^5}\\ &=\lim_{x\to0}\frac{\sin(x-\sin(x))}{x^3}\frac{2\sin\left(\frac{x}{2}\right)\sin\left(\frac{\sin(x)}{2}\right)}{x^2}\\[6pt] &=\frac16\cdot\frac12\\[6pt] &=\frac1{12}\tag{14} \end{align} $$ Adding $(13)$ and $(14)$ gives $$ \color{#C00000}{\lim_{x\to0}\frac{x\sin(\sin(x))-\sin^2(x)}{x^6}=\frac1{18}}\tag{15} $$

Added Explanation for the Derivation of $(6)$

The explanation below works for $x\gt0$ and $x\lt0$. Just reverse the red inequalities.

Assume that $x\color{#C00000}{\gt}0$ and $|x|\lt\pi/2$. Then $\tan(x)-2\tan(x/2)\color{#C00000}{\gt}0$.

$(3)$ is equivalent to $$ \begin{align} &(-1/2-\epsilon)(\tan(x)-2\tan(x/2))\\[4pt] \color{#C00000}{\le}&\sin(x)-2\sin(x/2)\\[4pt] \color{#C00000}{\le}&(-1/2+\epsilon)(\tan(x)-2\tan(x/2))\tag{16} \end{align} $$ for all $|x|\lt\delta$. Thus, for $k\ge0$, $$ \begin{align} &(-1/2-\epsilon)(2^k\tan(x/2^k)-2^{k+1}\tan(x/2^{k+1}))\\[4pt] \color{#C00000}{\le}&2^k\sin(x/2^k)-2^{k+1}\sin(x/2^{k+1})\\[4pt] \color{#C00000}{\le}&(-1/2+\epsilon)(2^k\tan(x/2^k)-2^{k+1}\tan(x/2^{k+1}))\tag{17} \end{align} $$ Summing $(17)$ from $k=0$ to $\infty$ yields $$ \begin{align} &(-1/2-\epsilon)\left(\tan(x)-\lim_{k\to\infty}2^k\tan(x/2^k)\right)\\[4pt] \color{#C00000}{\le}&\sin(x)-\lim_{k\to\infty}2^k\sin(x/2^k)\\[4pt] \color{#C00000}{\le}&(-1/2+\epsilon)\left(\tan(x)-\lim_{k\to\infty}2^k\tan(x/2^k)\right)\tag{18} \end{align} $$ Since $\lim\limits_{k\to\infty}2^k\tan(x/2^k)=\lim\limits_{k\to\infty}2^k\sin(x/2^k)=x$, $(18)$ says $$ \begin{align} &(-1/2-\epsilon)(\tan(x)-x)\\[4pt] \color{#C00000}{\le}&\sin(x)-x\\[4pt] \color{#C00000}{\le}&(-1/2+\epsilon)(\tan(x)-x))\tag{19} \end{align} $$ which, since $\epsilon$ is arbitrary is equivalent to $(6)$.

share|improve this answer
Cool ....... +1 –  user1551 Jul 7 '13 at 13:15
(+1) Side note: it is easier to reinvent L'Hopitale's rule than come up with this solution. I bet that authors of the book didn't bother much about methods avaliable to students when they were suggesting this problem –  Norbert Jul 7 '13 at 14:48
@Norbert It is rather naive to say that (essentially, sloppy or careless) about G. H. Hardy. –  Andres Caicedo Jul 7 '13 at 15:03
You like challenge, don't you? I think Hardy made a joke, here. –  1015 Jul 7 '13 at 15:43
@AndresCaicedo I will not change my mind even if now I realized that the author of the book is G. H. Hardy. I saw quite enough problems in books of well known mathematicians which far away from the level of other problem of a particular paragraph. –  Norbert Jul 7 '13 at 16:03

Lemma. $\lim\limits_{x\to0}\dfrac{x-\sin(x)}{x^3}=\dfrac16$.

Proof of lemma. To prove this lemma, we will mainly follow robjohn's idea, but using a different proof. Since $\dfrac{x-\sin(x)}{x^3}$ is an even function, it suffices to prove that the right hand limit is equal to $\frac16$. For any fixed $0<x<\frac\pi2$, let $x_n = 2^{-n}x$ for $k=0,1,2,\ldots$. Then $$ \dfrac{\sin x_n}{x_n}=\frac{\sin(2x_{n+1})}{2x_{n+1}}=\frac{2\sin(x_{n+1})\cos(x_{n+1})}{2x_{n+1}}\le\frac{\sin(x_{n+1})}{x_{n+1}}. $$ So, $\color{red}{y_n} = \dfrac{\sin x_n}{x_n}$ is an increasing sequence. Now \begin{align*} \frac{\sin(x)-x}{x^3} &= \sum_{k=0}^n \frac{2^k\sin(x_k)-2^{k+1}\sin(x_{k+1})}{x^3} + \frac{2^{n+1}\sin(x_{n+1})-x}{x^3}\\ &= \sum_{k=0}^n \frac{2^{k+1}\sin(x_{k+1})\cos(x_{k+1})-2^{k+1}\sin(x_{k+1})}{x^3} + \frac{2^{n+1}\sin(x_{n+1})-x}{x^3}\\ &= -\sum_{k=0}^n \frac{2^{k+2}\sin(x_{k+1})\sin^2(x_{k+2})}{x^3} + \frac{\sin(x_{n+1})/x_{n+1} - 1}{x^2}\\ &= -\sum_{k=0}^n \frac{y_{k+1}y_{k+2}^2}{2^{2k+3}} + \frac{\sin(x_{n+1})/x_{n+1} - 1}{x^2}. \end{align*} Therefore \begin{align*} \frac{\sin(x)-x}{x^3} \begin{cases} \ge -\sum_{k=0}^n \frac{1}{2^{2k+3}} + \frac{\sin(x_{n+1})/x_{n+1} - 1}{x^2},\\ \le -\sum_{k=0}^n \frac{y_1^3}{2^{2k+3}} + \frac{\sin(x_{n+1})/x_{n+1} - 1}{x^2}. \end{cases}\tag{1} \end{align*} As $\sum_{k=0}^\infty \frac{1}{2^{2k+3}} = \frac16$, by taking $n$ to infinity in $(1)$, we get $$ -\frac16 \le \frac{\sin(x)-x}{x^3} \le -\frac{y_1^3}6. $$ Let $x\to0^+$, the result follows.

We are now ready to answer the OP's question.

Solution. Let $s=\sin(x)$. We have \begin{align*} &x \sin(s) - s^2\\ =&x \sin(s-x+x) - s^2\\ =&x \sin(s-x)\cos(x) + x\sin(x)\cos(s-x) - s^2\\ =&-x \sin(x-s)\cos(x) + xs \cos(x-s) - s^2\\ =&-x \sin(x-s)\cos(x) + xs - s^2 - xs(1 - \cos(x-s))\\ =&-x \sin(x-s)\cos(x) + x(x-s) - (x-s)^2 - xs(1 - \cos(x-s))\\ =&\underbrace{x((x-s)-\sin(x-s))\cos(x)}_A + \underbrace{x(x-s)(1-\cos(x))}_B - \underbrace{(x-s)^2}_C - \underbrace{xs(1 - \cos(x-s))}_D\\ =&A + B - C - D. \end{align*} Now \begin{align*} \lim_{x\to0}\frac{A}{x^6} &=\lim_{x\to0}\frac{(x-s)-\sin(x-s)}{x^5} =\lim_{x\to0}\frac{(x-s)-\sin(x-s)}{(x-s)^3}\left(\frac{x-s}{x^3}\right)^3 x^4=0,\\ \lim_{x\to0}\frac{B}{x^6} &=\lim_{x\to0}\frac{(x-s)(1-\cos(x))}{x^5} =\lim_{x\to0}\frac{x-s}{x^3}\frac{2\sin^2(x/2)}{x^2} =\frac16\times 2(1/2)^2 = \frac1{12},\\ \lim_{x\to0}\frac{C}{x^6} &=\lim_{x\to0}\frac{(x-s)^2}{x^6} =\left(\frac16\right)^2 = \frac1{36},\\ \lim_{x\to0}\frac{D}{x^6} &=\lim_{x\to0}\frac{1 - \cos(x-s)}{x^4} =\lim_{x\to0}\frac{2\sin^2(\frac{x-s}2)}{x^4} =\lim_{x\to0}\frac{2\sin^2(\frac{x-s}2)}{(x-s)^2}\left(\frac{x-s}{x^3}\right)^2x^2 =0. \end{align*} Therefore $\lim\limits_{x\to0}\dfrac{x \sin(s) - s^2}{x^6}=\dfrac1{12}-\dfrac1{36}=\dfrac1{18}$.

share|improve this answer
Your solution is particularly appealing once we get the limit $(x - \sin x)/x^{3}$. Way better than what I presented in my blog post. –  Paramanand Singh Jul 8 '13 at 3:57
@ParamanandSingh Thanks. Your question is very interesting. I really enjoy this fun exercise. –  user1551 Jul 8 '13 at 12:15

I could prove it without using L'Hospital's rule, though I needed the following formula for $\sin x$ $$\sin{x}=x\prod_{k=1}^\infty\left(1-\frac{x^2}{k^2\pi^2}\right)=x\left(1-\frac{x^2}{6}+\frac{x^4}{120}+O(x^6)\right)$$ and the observation $$\sin ^2x=x^2\left(1-\frac{x^2}{3}+O(x^4)\right)$$ The constants $1/6$ and $1/120$ are due to $\zeta(2)/\pi^2$ and $\frac{1}{2}(\zeta^2(2)-\zeta(4))$ respectively. I also have used the simple formula $$\lim_{x\rightarrow 0}\frac{\sin x}{x}=1$$

Now I start the proof \begin{equation} \begin{split} \ &\lim_{x\rightarrow 0}\frac{x\sin(\sin x)-\sin^2x}{x^6}\\ \ = & \lim_{x\rightarrow 0}\frac{x\sin x \left(\prod_{k=1}^\infty\left(1-\frac{\sin^2x}{k^2\pi^2}\right)\right)-\sin^2x}{x^6}\\ \ =&\lim_{x\rightarrow 0}\frac{\sin x}{x} \lim_{x\rightarrow 0}\frac{x \left(\prod_{k=1}^\infty\left(1-\frac{\sin^2x}{k^2\pi^2}\right)\right)-x\prod_{k=1}^\infty\left(1-\frac{x^2}{k^2\pi^2}\right)}{x^5}\\ \ =&\lim_{x\rightarrow 0}\frac{(1-\frac{\sin^2x}{6}+\frac{\sin^4 x}{120}+O(\sin^6x))-(1-\frac{x^2}{6}+\frac{x^4}{120}+O(x^6))}{x^4}\\ \ =&\lim_{x\rightarrow 0}\frac{1-\frac{\sin^2x}{x^2}}{6x^2}+\lim_{x\rightarrow 0}\frac{\sin^4x-x^4}{120x^4}\\ \ =&\lim_{x\rightarrow 0}\frac{1-(1-\frac{x^2}{3}+O(x^4))}{6x^2}+\frac{1}{120}(1-1)\\ \ =&\frac{1}{18}\hspace{0.6cm} \Box \end{split} \end{equation}

share|improve this answer
There is nothing wrong in your derivation Samrat, but somehow your solution seems to be too complicated for a question in an introductory chapter on limits. I am searching for a solution which can be presented to a person who is learning limits and has the will to try challenging problems. –  Paramanand Singh Jul 7 '13 at 9:35
Yes, I admit that to follow my derivation the person has to know the Euler's product formula for sin(x). But otherwise, it is just manipulation. Also you don't need to place those big-Oh notations there, I just put them for brevity. –  Samrat Mukhopadhyay Jul 7 '13 at 9:39
Just before this problem in the book, there is a simpler limit $$\lim_{x \to 0}\frac{1 - \cos(1 - \cos x)}{x^{4}}$$ which can be easily solved if write $$1 - \cos(1 - \cos x) = 1 - \cos\left(2\sin^{2}\frac{x}{2}\right) = 2\sin^{2}\left(\sin^{2}\frac{x}{2}\right)$$ and I am trying to find a solution similar to this. –  Paramanand Singh Jul 7 '13 at 10:23
yes, i also saw that. I was also trying to find something similar, but for this problem it was not working. So I thought I should post this solution, because it does not use L'Hospital. Well maybe there is a simple one, we have to carry on the search for that. –  Samrat Mukhopadhyay Jul 7 '13 at 10:29

For an elementary proof, I’m sure those that have been given are pretty much what Hardy had in mind. But if you want to use the Taylor (Maclaurin) expansion of the sine, then it’s really easy. The function $\sin\circ\sin$ has the expansion $x-x^3/3+x^5/10$, ignoring terms of degree $7$ and higher; this is perfectly easy to do by hand. And the expansion of $\sin^2$ is $x^2-x^4/3+2x^6/45$, even easier. The first term in the desired difference is $x^6/18$, and there you are.

share|improve this answer
Lubin, I agree fully with what you say. It would have been better if we were allowed to use series expansions. But as I said the book expects this question to be solved using preliminary techniques. –  Paramanand Singh Jul 8 '13 at 4:10

$\eqalign{ L \;&=\; \lim\limits_{x \to 0} \dfrac {x-\sin x} {x^3} \\ \;&=\; \lim\limits_{t \to 0} \dfrac {3t-\sin 3t} {27t^3}\qquad x=3t \\ \;&=\; \lim\limits_{t \to 0} \dfrac{3t-3\sin t+4\sin^3t}{27t^3}\qquad \sin3t=3\sin t-\sin^3t \\ \;&=\; \dfrac19\lim\limits_{t \to 0} \dfrac{t-\sin t}{t^3}+\dfrac4{27}\lim\limits_{t\to0}\dfrac{\sin^3t}{t^3} \\ \;&=\; \dfrac L9+\dfrac4{27} \\ \;&\Rightarrow\;\;\,\text{we obtain }\, L=\dfrac16 }$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.